Living with germs : in sickness and in health - Playfair, J. H. L. (Oxford University Press, 2004)
The vast majority of germs, also known as microbes, do not infect us at all: it is pathogens that make us ill. These include bacteria, viruses, protozoa, fungi, worms, and prions. In Living with Germs, renowned expert John Playfair vividly describes these pathogens and the defence mechanisms by which we come to terms with them, whether by eliminating them, stopping them from eliminating us, or simply learning to live with them. A fascinating, occasionally. gruesome, but always utterly compelling read. - ;The word germ is defined as 'a microbe that causes disease'. The vast majority of microbes.